Gambaran Pelayanan Administrasi Pendaftaran Rawat Jalan Pasien BPJS Selama Masa Pandemi Covid-19 Di Rumah Sakit Al Islam Bandung Tahun 2021: . - Hanafi, Mutiafani; Winarti, Wiwin; Rihadatul'aisy, Kamila Rostiana (JURNAL TERAS KESEHATAN, 2022)
The title of this research is "Overview of BPJS Outpatient Registration Administration Services during COVID-19 Pandemic at Al Islam Hospital Bandung in 2021". The purpose of this research was to determine the outpatient registration administrative services provided to BPJS patients. This research was conducted from April to June 2021. The type of research used is using a qualitative method with a descriptive approach, while the data collection technique is through a document review process, interviews with the registration supervisor and several staff who served as implementers and also observations carried out in the outpatient registration unit of BPJS patients. The collected data is then analyzed and described in a detailed and structured manner. The results of this research are the process of implementing registration services refers to the applicable regulations and also the provisions that have been made by the hospital. Some of the registration services at Al Islam Hospital that can be used by BPJS patients are, Direct Registration, Telephone Registration, Autoregistration, Referrals between health facilities, and Internal Referrals. From these data it is concluded that the services provided by Al Islam Hospital during the pandemic has made the necessary modifications to the existing regulation